GLOBALIZATION AND ASSAMESE BIHU: CULTURAL CONTINUITY AND CHANGE - Nath, Swapan Jyoti (International Journal of Research -GRANTHAALAYAH, 2019)
Globalization, as a transformative socio-economic and cultural phenomenon, has had far-reaching implications for local traditions worldwide. In the Indian context, regional festivals like Assamese Bihu, a cornerstone of Assamese cultural identity, have witnessed dynamic shifts under the influence of global interconnectedness. This paper explores the evolving nature of Bihu in response to globalization, examining the balance between cultural preservation and transformation. It analyzes how Bihu traditionally a community-centric agrarian festival, has adapted to modernity through media, diasporic engagement, commercialization, and cross-cultural exposure.